Handbook of food safety engineering - Sun, Da-Wen. (Oxford : Wiley-Blackwell, 2011)
'This book presents a comprehensive and substantial overview of the emerging field of food safety engineering, bringing together in one volume the four essential components of food safety: the fundamentals of microbial growth food safety detection techniques microbial inactivation techniques food safety management systems Written by a team of highly active international experts with both academic and professional credentials, the book is divided into five parts. Part I details the principles of food safety including microbial growth and modelling. Part II addresses novel and rapid food safety detection methods. Parts III and IV look at various traditional and novel thermal and non-thermal processing techniques for microbial inactivation. Part V concludes the book with an overview of the major international food safety management systems such as GMP, SSOP, HACCP and ISO22000'--Provided by publisher.
Includes bibliographical references and index.
Print version record.
Keywords: Food -- Safety measures; Food -- Microbiology; Food industry and trade -- Sanitation; Electronic books